Peranan Akuntansi Pertanggung Jawaban dalam Pengendalian Manajemen pada Bank Syariah - Nor Firman, Rachmad; Faizun, Dikril (Tasharruf : Journal of Islamic Economics and Business, 2020)
The form of line management accountability in Islamic banks is something that needs to be considered. Accountability needs to be pursued because this is to protect assets from theft, embezzlement, misuse or placement of assets in inappropriate locations. Thus, every line management of Islamic banks needs to use responsibility accounting as a control in management control. Accountability accounting in Islamic banking is present because of the decentralized form of responsibility and authority applied by the top management of the Islamic bank. effectiveness and efficiency as well as the state of the bank they lead. So that top management can make the right business decisions for the existence of Islamic banks in the future.